(untitled) (REMUNOM, 2026)
This article analyzes the legal limits of freedom of expression on social media and the mechanisms for accountability for abuses in the digital environment. It starts from the premise that freedom of expression constitutes a fundamental right guaranteed by the 1988 Federal Constitution and an essential element of the Democratic Rule of Law, as it guarantees the pluralism of ideas and the free expression of thought. However, this right is not absolute and must be exercised in harmony with other fundamental rights, such as honor, image, privacy, and human dignity. The objective of this research is to examine how the Brazilian legal system establishes a balance between the protection of freedom of expression and accountability for illicit conduct on social media. To this end, a qualitative and exploratory approach was adopted, based on a literature review and documentary analysis of doctrine, legal provisions, and jurisprudential precedents from the superior courts. The results indicate that the expansion of digital technologies has significantly broadened the reach of individual expressions, intensifying conflicts between freedom of expression and personality rights. In this context, the Brazilian, the Law No. 12.965/2014, Internet Bill of Rights, establishes parameters by conditioning the civil liability of providers on non-compliance with a court order to remove illicit content. This study contributes to the understanding of the legal criteria used by the Brazilian legal system in reconciling freedom of digital expression with accountability for abuses in the virtual environment.